Fe3O4@Poly-dopamine as T2W MR Nanoprobe for breast cancer detection and as inhibitory Agent in Helicobacter Pylori - Mohammad Ghaderian; Mohammad Reza Salamat; Daryoush Shahbazi-Gahrouei; Fahimeh Hossein Beigi; Amir Sajedi; Gholamreza Amiri; Tahmineh Narimani (Nanomedicine Journal)
Objective(s): Recently, magnetic nanoparticles coated with different ligands have been utilized in diagnosis, drug delivery, and therapy. This study aimed to synthesize,  characterize, and apply Fe3O4 coated with Poly Dopamine (PDA) as an MR imaging nanoprobe and its application in metronidazole-resistant helicobacter pylori (H.pylori).Materials and Methods: Fe3O4 nanoparticles were characterized and their cytotoxicity was determined in MCF-7 cell lines. Then, coated and non-coated nanoparticles were injected intravenously into  9 xenograft BALB/C mice, and the signal intensity of the T2-weighted MR was assessed. Iron concentrations were measured by ICP-AES, and histopathological assessment was done on harvested critical organs. Finally, The standard disk diffusion method was also used to identify the H.pylori resistance to metronidazole. The minimum inhibitory concentrations and the minimum bactericidal concentration of uncoated and coated iron oxide nanoparticles were investigated.Results: The MTT assay showed low cytotoxicity at 512 µg/ml. T2 relaxation times of tumors were lower compared to normal tissues. ICP-AES results indicated that the NPs accumulated mostly in the spleen and liver. The histopathology study demonstrated that the vital organ tissues had less morphologic abnormality and apoptotic changes. The minimum inhibitory and minimum bactericidal concentrations of ION@PDA were 16-64 µg/ml and 16-128 µg/ml, respectively. Conclusion: Due to the high permeability of nanoprobes in tumors, less cytotoxicity, and its inhibitory effects on metronidazole-resistant H.pylori, ION@PDA may be used as a nano contrast agent in MR imaging for the detection of MCF-7 cells.